2021
DOI: 10.1111/jar.12886
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of therapists providing psychological treatment for adults with depression and intellectual disabilities as part of a randomised controlled trial

Abstract: Background Health professionals were trained to deliver adapted psychological interventions for depression to people with learning disabilities and depression alongside a supporter. Exploring the delivery of psychological interventions can help increase access to therapy. Method Twenty‐seven participants took part in six focus groups, and the data were subject to a Framework Analysis. Results The structure and focus of the manualised therapies, and the use of specific techniques were perceived as key to servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Practical resources provided during the training, such as examples of ACT-consistent feedback, practise in drafting written feedback using the case examples, and continued opportunities for practice and supervision, also increased confidence and facilitated greater acceptability among the therapists. These findings support the wider findings, which suggested that getting more experience in delivering the intervention over time was key to developing mastery of the therapeutic approaches and increased confidence (Smith et al, 2021). It has been previously reported that those trial therapists who felt satisfied with training and supervision received were more likely to participate in the delivery of a similar type of intervention in the future (Rodda et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Practical resources provided during the training, such as examples of ACT-consistent feedback, practise in drafting written feedback using the case examples, and continued opportunities for practice and supervision, also increased confidence and facilitated greater acceptability among the therapists. These findings support the wider findings, which suggested that getting more experience in delivering the intervention over time was key to developing mastery of the therapeutic approaches and increased confidence (Smith et al, 2021). It has been previously reported that those trial therapists who felt satisfied with training and supervision received were more likely to participate in the delivery of a similar type of intervention in the future (Rodda et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the BeatIt and StepUp therapists in the study felt that developing a strong grasp of the interventions gave them the confidence and know how to adapt their approach to meet the particular needs of the individuals they worked with (Smith et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We encourage therapists to use their experience and creativity to personalise the treatment of depression, in the context of a clear therapeutic approach. Interestingly, the BeatIt and StepUp therapists in the study felt that developing a strong grasp of the interventions gave them the confidence and know how to adapt their approach to meet the particular needs of the individuals they worked with (Smith et al 2021).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…People with mild IDs receive support and treatment from various types of services, such as ID services, community social care, mainstream mental health services, non-acute and acute psychiatric services and emergency departments (Standen et al 2016;Whittle et al 2018). Forming a valuable and meaningful relationship with a professional contributes greatly to both the quality of life and support for people with mild IDs and therapeutic outcomes (Embregts 2020;Evans & Randle-Phillips 2020;Smith et al 2020). In general client populations, this sense of alignment between healthcare professionals and clients is commonly referred to as the working alliance.…”
mentioning
confidence: 99%
“…Forming a valuable and meaningful relationship with a professional contributes greatly to both the quality of life and support for people with mild IDs and therapeutic outcomes (Embregts 2020 ; Evans & Randle‐Phillips 2020 ; Smith et al . 2020 ). In general client populations, this sense of alignment between healthcare professionals and clients is commonly referred to as the working alliance.…”
mentioning
confidence: 99%